Germinação e vigor em genótipos de trigo sob estresse salino e déficit hídrico - Olivo, Mateus (2013)
Wheat (Triticum aestivum L.) is the third most produced worldwide cereal. In Brazil more than half of the consumed wheat is imported. The species has hexaploid genome, which gives good adaptation to different environmental conditions and tolerance to abiotic stresses. Among the main factors that cause stress can be highlighted the problem of drought and soil salinity. Water deficit is the low availability of water to plants, affecting their growth and development caused death when drastic. The salinity is the high salt concentrations in the soil. Therefore, the objective of this study was to evaluate the performance of 14 wheat genotypes when subjected to salt stress and water deficit during the germination phase. To simulate the salt stress were used three solutions with different NaCl concentrations (44.83, 89.66 and 134.49mM NaCl) and a control treatment, pure water. To water deficit were used three solutions with different concentrations of polyethylene glycol 6000 plus pure water control treatment, providing four different osmotic potentials (0.0, -0.2, -0.4 and -0.6MPa). Germination, first count of germination, speed of germination index, shoot dry matter, root dry matter, shoot length and root length were reduced due to the increase of NaCl concentration and osmotic potential more negative. The Marfim genotype was shown to be more tolerant to salt stress and also the stress by water deficit. The CSR test is a potential indicator for identification of genotypes tolerant to salt stress and water deficit. The test GERM is a potential indicator to identify genotypes tolerant to water stress.